Obsessies : van wunderkammer tot cyberspace. - Vroege, Bas; Mader, Donald; Druckery, Timothy; Langford, Martha; Mulder, Arjen; Rijksmuseum Twenthe, Enschede; Foto Biennale Enschede 1995 Netherlands (Enschede : Foto Biennale Enschede, 1995)
Aziz & Cucher ; Baltz, Lewis ; Blaszk, Neville ; Buchana, Hamisch ; Burkart, Manuela ; Chevallier, Florence ; Courchesne, Luc ; Cumming, Donigan ; Eddie D. ; Dement, Linda ; Divola, John ; Feldmann, Hans-Peter ; Fontcuberta, Joan ; Fritz, Darko ; Geleynse, Wyn ; Germain Julian ; et al.
This book appears in connection with the Foto Biennale Enschede 1995 ... November 3-26 1995
kunstcatalogus